The Reality of Development Process in Syria between Central Market Policy and Free Market Economy/Analytical-Historical Study/ - Mohammad, Osama; Moalla, Ferias (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The observer of economical development process in Syria realizes that the economical policy wasn’t one consistent policy throughout successive phases of time. The adopted policies were dependant on the market economy once and on central planning in alter phase. Finally the government proceeded with adopting social market economy. These various polices were the most dominant features that distinguished the developmental process through the history of Syria since the independence up to 2010. All that was set against a backdrop of many changes the country witnessed since then. The current study is dedicated to reveal the reality of development in Syria in the light of a adopting different economical policies in their management. Moreover, it uncovers the reasons behind adopting various policies. It, as well, compares between the two policies in order to know the more efficient and able in managing the economical and social development successfully in Syria. The outcomes of this study show that the development process in Syria was subject to dynamic vagaries related to the political speech and the realistic surrounding conditions circum stances both the regional and international. It needs scientific economical formulation that provides adopting developmental policy away from ideological and political strife.